Kebijakan Sistem Pemerintahan E-Government di Kabupaten Tulungagung - Soesetyo, Achmad Boedi; Kasiyanto, Kasiyanto (Universitas Muhammadiyah Sidoarjo, 2013)
This study aimed to identify and analyze the implementation of electronic government system (e-government) in Tulungagung Sub-district, to identify and analyze the attitudes and access Tulungagung bureaucrats towards information technology, to identify and analyze Tulungagung bureaucrats and Tulungagung towards e-government policy, and to identify and analyze models of electronic government system (e-government) in accordance with the community's social base in Tulungagung. The methods of this study used qualitative research. Based on the results of this study indicated that the attitudes and access bureaucrats may accept the use of telematics on e-government policy, but the development and use of telematics in Tulungagung is still far from ideal conditions to support e-government policies. This is because they did not had a mature level of readiness to accept the program of e-government policies and require the formulation of a model system should be built based on the clarity of the vision and mission of the Tulungagung Government.